Asteroidea, Echinoidea y Holothuroidea en fondos someros de la Bahía de Loreto, Baja California Sur, México - Holguin Quiñones, Oscar (2000)
To evaluate echinoderm distribution, abundance and density a double 50 m transect, with a side observation range of 2.5 m was used at each of 11 stations (bimonthly samplings, Aug. 1997-Febr. 1998). In Bahía de Loreto the Phylum Echinodermata consists of 26 taxa. The greatest mean abundance by transect and mean densities in order of importance for Echinoidea were: Echinometra vanbrunti (94.1±52.9 ind, 0.25 ind/m2), Centrostephanus coronatus (38.15±9.15 ind, 0.06 ind/m2), Tripneustes depressus (28.68 ±6.86 ind, 0.039 ind/ m2), Eucidaris thouarsii (10.66±3.37 ind, 0.025 ind/m2) and Diadema mexicanum (11.75±4.92 ind, 0.023 ind/ m2); for Asteroidea were: Phataria unifascialis, Mithrodia bradleyi and Acanthaster planci. Asteroidea was the dominant class with 12 species, followed by Echinoidea with ten and Holothuroidea was represented by four species.